1983
DOI: 10.1007/bf00140471
|View full text |Cite
|
Sign up to set email alerts
|

The lens and PUVA therapy

Abstract: A study was made of patients, who were receiving PUVA therapy for psoriasis, to see if lens abnormalities occurred which could be due to the PUVA treatment. In a group of 42 patients there was only one eye of one patient, in which a very slight opacity was found which might possibly have developed during the therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…References published between 1980 and December 2010 in the PubMed, Embase and Cochrane databases, in English and French, were reviewed using the key words ‘Psoriasis’ AND’phototherapy’ OR ‘ultraviolet therapy’ OR ‘UVA’ OR ‘UVB’ OR ‘PUVA’ OR ‘photochemotherapy’ AND ‘ocular’ OR ‘cataract’ OR ‘eye’ OR ‘lens’ Of the 30 references found, 12 were eliminated by reading the title or abstract (eight did not concern PUVA, two did not concern psoriasis, one was a case report, one was a review). and five after reading the article We finally selected 13 studies: seven were prospective 5–11 and six were retrospective 12–17 . All studies concerned exclusively PUVA therapy.…”
Section: Risk Of Ocular Damage In Prospective Cohort Studies Other mentioning
confidence: 99%
See 2 more Smart Citations
“…References published between 1980 and December 2010 in the PubMed, Embase and Cochrane databases, in English and French, were reviewed using the key words ‘Psoriasis’ AND’phototherapy’ OR ‘ultraviolet therapy’ OR ‘UVA’ OR ‘UVB’ OR ‘PUVA’ OR ‘photochemotherapy’ AND ‘ocular’ OR ‘cataract’ OR ‘eye’ OR ‘lens’ Of the 30 references found, 12 were eliminated by reading the title or abstract (eight did not concern PUVA, two did not concern psoriasis, one was a case report, one was a review). and five after reading the article We finally selected 13 studies: seven were prospective 5–11 and six were retrospective 12–17 . All studies concerned exclusively PUVA therapy.…”
Section: Risk Of Ocular Damage In Prospective Cohort Studies Other mentioning
confidence: 99%
“…The retrospective studies 12–17 did not include internal or external comparators and therefore cannot provide a rigorous estimate of ocular risk following PUVA. By comparing the effect of the presence or absence of eye protection, Calzavara‐Pinton et al.…”
Section: Risk Of Ocular Damage In Prospective Cohort Studies Other mentioning
confidence: 99%
See 1 more Smart Citation
“…In-vitro studies of human lenses showed that the gamma crystalline fraction of the lens proteins of a young lens is much more sensitive to ultraviolet light than other fractions in the same lens or the same fractions in older lenses [7]. On the basis of mor- [5] 96 -Tegner '83 [13] 302 -Sterk '83 [12] 42 (1) Boukes '85 [1] 408 3 Recchia '86 [9] 200 -6 studies 1.094 3 (4) phological study, with the help of Scheimpflug lens-photography and densitometry, three age groups can be distinguished for the non-cataractous aging of the lens: up to 35 years (clear), 35 to 55 years (slight decrease in transparency, slight increase in thickness of lens) and above 55 years (more pronounced loss of transparency and further increase in thickness of lens) [11].…”
Section: Introductionmentioning
confidence: 99%